High-flexibility insulating material for VR equipment cable and preparation method of high-flexibility insulating material
The problem of insufficient insulation and flexibility performance is solved by using flexible block flame retardant copolymers, surface-modified banana leaf-shaped boron nitride and boron nitride in VR equipment cables, and the material system of Fe3O4 nanowires is achieved High flame retardant, excellent mechanical and electromagnetic shielding performance improves the comprehensive performance of VR equipment cables.
Patent Information
- Application Number
- CN202411687862.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2024-12-20
AI Technical Summary
The insulation materials of existing VR equipment cables have shortcomings in terms of insulation and flexibility, and it is difficult to take into account high insulation and high flexibility. The microstructure and interface design of the materials are not fine enough, making it difficult to meet the strict working conditions requirements of VR cables.
A material system that includes flexible block flame retardant copolymer, surface-modified banana leaf-shaped boron nitride and surface-modified boron nitride coated Fe3O4 nanowires is adopted to improve flame retardant performance through synergistic carbonization effect and pass vinyl The surface modification of trimethoxysilane improves the dispersion and interface binding force of nanofillers, and combines the crosslinking reaction initiated by di-tert-butyl peroxide to enhance the comprehensive performance of the material.
It significantly improves the flame retardant performance, mechanical properties and insulation performance of the material, improves the electromagnetic shielding effect and signal transmission quality, extends the service life of the cable, and meets the high-frequency signal transmission and mechanical performance requirements of VR equipment.
Smart Images

Figure CN119161650A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of cable insulation materials, and in particular to a high-flexibility insulation material for VR device cables and a preparation method thereof. Background Art
[0002] With the rapid development of virtual reality (VR) technology, VR devices are widely used in games, education, medical treatment and other fields. As a key component connecting VR headsets and host computers, VR device cables need to have excellent insulation and flexibility to ensure stable signal transmission and comfortable user experience. High insulation performance can effectively prevent signal leakage and interference during transmission, ensure picture clarity and audio fidelity, and enhance the immersiveness of VR experience. At the same time, the cable material must be flexible enough to adapt to the user's frequent movement and bending operations, avoid limiting the user's range of activities due to the rigidity of the cable, and extend the service life of the cable. Therefore, the development of high-insulation and high-flexibility VR device cable materials is of great significance to promote the further development and application of VR technology, and is expected to break through the current bottleneck of VR equipment in terms of transmission lines and provide users with a better VR experience.
[0003] However, the insulation materials currently used in VR equipment cables are still insufficient in meeting high insulation and high flexibility. For example, the Chinese patent application with publication number CN115073922A discloses a nuclear environment resistant cable insulation material, but the insulation performance of the obtained material needs to be further improved. For another example, the Chinese patent with authorization announcement number CN108137876B discloses a method for manufacturing a flexible cross-linked cable insulation material, which has good flexibility but is prone to signal attenuation during high-frequency transmission. The main reasons for these deficiencies include: first, it is difficult to balance the insulation and flexibility of the existing material system, and improving the flexibility of the material often sacrifices its insulation performance; second, the microstructure and interface design of the material are not fine enough, and it is difficult to achieve the synergistic effect of insulation and flexibility enhancement; third, there is a lack of material optimization and modification strategies for VR application scenarios, which makes it difficult to meet the harsh working conditions of VR cables. Therefore, it is urgent to develop a new insulation material system and modification method to give the material high flexibility while ensuring excellent insulation performance, so as to break through the technical bottleneck of VR cable transmission. Summary of the invention
[0004] (1) Technical issues solved The purpose of the present invention is to provide a high-flexibility insulating material for VR device cables and a preparation method thereof, so as to solve the problem that the current VR device cable insulating material has insufficient insulation and flexibility performance.
[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A highly flexible insulating material for VR equipment cables, comprising the following components by weight: 5-10 parts of a flexible block flame-retardant copolymer, 3-8 parts of surface-modified banana leaf-shaped boron nitride, 4-10 parts of surface-modified boron nitride-coated Fe3O4 nanowires, 30-55 parts of low-density polyethylene, 45-60 parts of butadiene-styrene copolymer, 0.2-0.9 parts of di-tert-butyl peroxide, 2-5 parts of ethylene-vinyl acetate copolymer, 1.0-3.5 parts of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 0.5-1.8 parts of ethoxyquinoline, and 1.5-3.5 parts of dioctyl phthalate; The flexible flame-retardant block copolymer is obtained by copolymerization of piperazine phosphate, melamine phosphate and diphenyl (siloxane and polysiloxane); The surface-modified banana leaf-shaped boron nitride is obtained by surface-modifying banana leaf-shaped boron nitride with vinyltrimethoxysilane; The surface-modified boron nitride coated Fe3O4 nanowires are obtained by surface-modifying the boron nitride coated Fe3O4 nanowires with 3-aminopropylmethyldimethoxysilane.
[0006] Furthermore, the preparation method of the flexible block flame-retardant copolymer is as follows: by weight, at room temperature, 50 to 70 parts of a binary block copolymer and 2 to 6 parts of diphenyl (siloxane and polysiloxane) are uniformly mixed and placed in a vacuum oven, dehydrated at 250 to 300° C. for 60 to 120 minutes, and then the temperature is reduced to 50 to 100° C., and the product is crushed in a crusher to obtain a flexible block copolymer.
[0007] Furthermore, the preparation method of the binary block copolymer is as follows: after uniformly mixing 48 to 70 parts of piperazine phosphate and 16 to 30 parts of melamine phosphate by weight, the binary block copolymer is obtained after dehydration reaction for 2 to 4 hours.
[0008] Furthermore, the preparation method of the diphenyl (siloxane and polysiloxane) is as follows: 30 to 45 parts by weight of diphenylsilanediol are placed in a vacuum oven, dehydrated at 160 to 200° C. for 1 to 3 hours, then taken out of the vacuum oven and crushed in a grinder to obtain diphenyl (siloxane and polysiloxane).
[0009] The present invention aims to design a new type of flexible block flame-retardant copolymer for improving the comprehensive performance of VR equipment cable insulation materials. This ternary block copolymer is composed of three flame-retardant groups, namely, silicon-containing, phosphorus-containing and nitrogen-containing. Through the synergistic effect between them, it can not only greatly improve the flame retardant properties of the insulation material, but also give the material excellent mechanical properties. The excellent flame retardant properties of the ternary block copolymer are mainly attributed to its unique molecular structure organization mode and the optimal content ratio of the flame retardant group. During the combustion process, a synergistic carbonization effect will occur between the silicon-containing group and the phosphorus-containing and nitrogen-containing groups, which promotes the formation of the carbon layer and improves the carbonization efficiency. This synergistic carbonization effect not only increases the amount of combustion residues, but also makes the carbon layer structure more dense and solid. A large number of dense carbon layers can play a role in heat insulation and barrier, hinder the release of combustible gases, thereby effectively reducing the combustion intensity and inhibiting the spread of fire. Therefore, with the help of the synergistic carbonization effect of the flame retardant group, the ternary block copolymer exhibits a flame retardant efficiency far higher than that of traditional flame retardants. In addition to excellent flame retardant properties, the ternary block copolymer also exhibits excellent mechanical properties, especially in impact strength and elongation at break. This is mainly due to its unique molecular structure. During the processing, the ternary block copolymer will form droplet-shaped particles, which will produce a larger contact area and stronger interaction with the polymer matrix, thereby enhancing the interfacial bonding force. Compared with other control flame retardants, the insulating material modified by the ternary block copolymer has higher impact strength and better flexibility. In summary, the present invention carefully designs the molecular structure and flame retardant group content of the ternary block copolymer, gives full play to the synergistic carbonization effect of silicon, phosphorus and nitrogen elements, and greatly improves the mechanical properties of the insulating material while ensuring excellent flame retardant properties. This ternary block copolymer with both high flame retardant efficiency and excellent mechanical properties will be expected to be used in fields such as VR equipment cables.
[0010] Furthermore, the preparation method of the surface modified banana leaf-shaped boron nitride is as follows: by weight, 40 to 60 parts of an ethanol aqueous solution with a volume fraction of 90% are prepared, and then the pH of the solution is adjusted to 4 with acetic acid, followed by adding 2 to 4 parts of vinyltrimethoxysilane, stirring at room temperature for 30 to 60 minutes, and then adding 3 to 7 parts of hydroxyl-grafted banana leaf-shaped boron nitride, stirring at 50 to 70° C. for 60 to 90 minutes, followed by suction filtration to obtain a filter residue, and then washing the filter residue three times with deionized water, and finally vacuum drying at 110 to 130° C. for 4 to 6 hours to obtain the surface modified banana leaf-shaped boron nitride.
[0011] Furthermore, the preparation method of the hydroxy-grafted banana leaf-shaped boron nitride is as follows: by weight, 2 to 5 parts of banana leaf-shaped boron nitride are dispersed in 30 to 50 parts of a 5 mol / L sodium hydroxide aqueous solution, and then stirred at 150 to 180° C. for 4 to 8 hours. After the reaction is completed, the solution is filtered to obtain a filter residue, and then the filter residue is rinsed with deionized water to a pH of 7, and finally dried completely in a vacuum drying oven at room temperature to obtain the hydroxy-grafted banana leaf-shaped boron nitride.
[0012] Further, the preparation method of the banana leaf-shaped boron nitride is as follows: by weight, at room temperature, 6 to 12 parts of sodium nitrate and 50 to 80 parts of concentrated sulfuric acid with a mass fraction of 80% are mixed uniformly, and then 10 to 25 parts of multi-walled boron nitride nanotubes and 3 to 9 parts of potassium permanganate are added, and then stirred for 90 to 120 minutes, and then the mixed solution is heated to 40 to 50 ° C and stirred for 25 to 40 minutes, and then 90 parts of deionized water are added, and the mixed solution is heated to 80 to 90 ° C, and the stirring is continued for 30 to 50 minutes, and then 3% hydrogen peroxide is added drop by drop, and the addition is stopped after the mixed solution does not generate gas, and then the filter residue is collected by vacuum filtration, and then the filter residue is washed with deionized water for 4 times, and finally the washed filter residue is vacuum dried at room temperature.
[0013] The present invention adopts the design of banana leaf-shaped boron nitride, which is mainly used to enhance the flexibility, strength and insulation performance of high-flexibility insulating materials for VR equipment cables. The main part of the banana leaf-shaped boron nitride is similar to a one-dimensional boron nitride nanotube, which is mainly used for enhancement. The edge part of the banana leaf-shaped boron nitride is similar to a boron nitride nanosheet, which has excellent flexibility and insulation. The banana leaf-shaped boron nitride combines the advantages of one-dimensional nanotubes and two-dimensional nanosheets. The unique morphology and structure of banana leaf-shaped boron nitride give it multiple enhancement and modification effects. As a new type of nanofiller, banana leaf-shaped boron nitride has both the high strength of one-dimensional nanotubes and the high flexibility of two-dimensional nanosheets. Introducing it into VR equipment cable insulation materials can improve the comprehensive performance of materials from multiple aspects. First, the main part of the banana leaf-shaped boron nitride is a hollow tubular structure similar to a one-dimensional boron nitride nanotube, which has extremely high mechanical strength and modulus. When an external force acts on the insulating material, the main trunk of the banana leaf-shaped boron nitride can act as a skeleton, bear the main load, and improve the tensile strength and compressive strength of the material. The nanotube structure can also hinder the expansion of cracks in the matrix and improve the fracture toughness of the insulating material. Secondly, the edge of the banana leaf-shaped boron nitride is similar to a two-dimensional boron nitride nanosheet, which is composed of a large number of layered boron nitrogen hexagonal atoms. The edge of this graphene-like structure gives the material excellent flexibility. When subjected to external force, the edge of the banana leaf can undergo reversible deformation, greatly improving the ductility of the material, so that the insulating layer can withstand repeated bending without cracking. At the same time, the presence of the layered structure also significantly improves the impact resistance of the material. In addition, the banana leaf-shaped boron nitride also has intrinsic high insulation. The band gap width of hexagonal boron nitride material is as high as 5~6eV, and it is difficult for electrons to be excited to form conductive carriers. After the introduction of banana leaf-shaped boron nitride, a large number of "insulating islands" are dispersed in the polymer matrix, which can effectively block the conductive path, improve insulation resistance, reduce dielectric loss, and reduce the risk of failure caused by leakage. Banana leaf-shaped boron nitride not only has excellent comprehensive performance itself, but also can produce a synergistic enhancement effect with the polymer matrix. On the one hand, there are a large number of interfaces between the banana leaf-shaped filler and the matrix, and the filler plays a physical reinforcement role on the matrix; on the other hand, the functionalized banana leaf-shaped boron nitride can form chemical bonds with the matrix, and the interface bonding force is stronger. Good interfacial compatibility ensures the effective transfer of load between the filler and the matrix, reduces stress concentration, and improves the service life of the material. It is worth mentioning that banana leaf-shaped boron nitride also has a low dielectric constant, which is crucial for VR equipment cable insulation materials. The dielectric constant of boron nitride materials is usually between 2 and 4, which is significantly lower than that of most polymer matrices. Introducing banana leaf-shaped boron nitride with a low dielectric constant as a filler can regulate and reduce the overall dielectric constant of the insulating material. A lower dielectric constant means that the material is less polarized and stores less energy at the same electric field strength, which helps to reduce the attenuation and distortion of the transmitted signal and improve the signal integrity and fidelity of the cable.In addition, the reduction in dielectric constant can also reduce the equivalent capacitance of the insulating layer, thereby reducing the RC delay of the transmission line and increasing the signal transmission rate. On the whole, the unique low dielectric properties of banana leaf-shaped boron nitride can significantly improve the signal transmission quality of VR cables and enhance the user's immersive experience. In summary, banana leaf-shaped boron nitride cleverly combines the high strength of one-dimensional nanotubes and the high toughness of two-dimensional nanosheets. Through its unique morphology and structure, it gives VR cable insulation materials excellent mechanical properties, flexibility and insulation. The multiple synergistic effects between banana leaf-shaped boron nitride and the polymer matrix further improve the comprehensive performance of the composite material. In addition, the low dielectric properties of banana leaf-shaped boron nitride can also improve the signal transmission quality of VR cables and enhance user experience. This high-performance insulating material is expected to promote the further development of VR technology and broaden its application space. The banana leaf-shaped boron nitride designed by the present invention and its enhancement mechanism provide new ideas for the development of new nanocomposite insulating materials.
[0014] The present invention introduces vinyl trimethoxy silane molecules into banana leaf-shaped boron nitride through hydroxylation and silanization surface modification to improve the compatibility and interface bonding between boron nitride and a matrix. The unique morphology and structure of banana leaf-shaped boron nitride give it excellent mechanical properties, insulation and thermal conductivity, but its application is often limited by problems such as poor compatibility with a polymer matrix and low dispersibility. In order to give full play to the strengthening and modifying effects of banana leaf-shaped boron nitride, its surface must be reasonably designed and chemically modified. The vinyl trimethoxy silane molecules used in the present invention are introduced into the surface of banana leaf-shaped boron nitride to prevent it from falling off during the processing of the composite material. At the same time, the organic vinyl functional group in the vinyl trimethoxy silane molecule can significantly increase the surface free energy of banana leaf-shaped boron nitride and improve its affinity with an organic polymer matrix. Secondly, after the surface modification of banana leaf-shaped boron nitride, its dispersibility and compatibility are significantly improved. The modified banana leaf-shaped boron nitride can be evenly dispersed in the matrix to avoid agglomeration, and give full play to its strengthening and modifying effects. The synergistic effect of physical entanglement and chemical bonding between filler and matrix makes stress transfer between interfaces more effective, significantly improving the mechanical properties of composite materials. In addition, closer contact between filler and matrix also contributes to the transmission of phonons at the interface, improving the thermal conductivity of composite materials. In summary, the present invention ingeniously utilizes vinyltrimethoxysilane molecules to carry out surface modification of banana leaf-shaped boron nitride, and introduces silane chemical bonding and vinyl groups to significantly improve the dispersibility of filler and compatibility with matrix. The improved interface combines the excellent mechanical, insulation and thermal conductivity of banana leaf-shaped boron nitride itself to the polymer matrix to the maximum extent, giving the composite material excellent comprehensive performance. The present invention provides a new idea for the preparation of high-performance boron nitride modified polymer composite materials, which is of great significance for the design of functional polymer materials.
[0015] Furthermore, the preparation method of the surface modified boron nitride coated Fe3O4 nanowires is as follows: 3 to 8 parts of boron nitride coated Fe3O4 nanowires are added to 100 parts of a mixed solution of ethanol and water in a mass ratio of 1:1, and then 1.0 to 3.5 parts of 3-aminopropylmethyldimethoxysilane are added, followed by magnetic stirring for 5 to 10 hours, and finally the solid powder is filtered and dried completely in a vacuum drying oven at room temperature.
[0016] Furthermore, the preparation method of the boron nitride coated Fe3O4 nanowires is as follows: by weight, 10 to 16 parts of sodium borohydride and 13 to 20 parts of ammonium chloride are dissolved in 100 parts of deionized water and mixed evenly, then 20 to 45 parts of Fe3O4 nanowires are added thereto, stirred at room temperature for 60 to 120 minutes, and then the solution is filtered to separate the solid powder and dried completely in a vacuum drying oven at room temperature, and then the completely dried solid powder is placed in a tubular furnace, and heat treated at 500 to 600°C for 60 to 120 minutes in an ammonia atmosphere to obtain boron nitride coated Fe3O4 nanowires.
[0017] Furthermore, the preparation method of the Fe3O4 nanowires is as follows: 3 to 8 parts of ferrous sulfate and 2 to 6 parts of sodium thiosulfate are added to a Teflon-lined autoclave, and then 10 parts of polyethylene glycol, 20 parts of deionized water and 10 to 20 parts of sodium hydroxide are added, followed by keeping warm at 140 to 160°C for 20 to 35 hours, and then centrifuging the solid product, washing the solid product three times with ethanol, and finally drying it completely under vacuum at room temperature to obtain Fe3O4 nanowires.
[0018] The purpose of the present invention to use surface-modified boron nitride to coat Fe3O4 nanowires is to enhance the comprehensive performance of VR equipment cable insulation materials, including electromagnetic shielding effect, dielectric properties, insulation properties and mechanical properties. By coating a boron nitride layer on the surface of the Fe3O4 nanowire and further performing surface silanization modification, the electromagnetic shielding effectiveness and interface compatibility of the nanowire can be significantly improved, thereby obtaining a high-performance cable insulation composite material. Boron nitride is an excellent insulating material with high resistivity, low dielectric loss and good chemical stability. Coating the boron nitride layer on the surface of the Fe3O4 nanowire can play the role of insulating shielding, prevent direct contact between the Fe3O4 nanowires, and reduce charge transfer and energy loss. At the same time, the boron nitride layer can also protect the Fe3O4 nanowires from erosion by the external environment, thereby improving the stability and reliability of the material. A core-shell structure is formed between the boron nitride coating layer and the Fe3O4 nanowire core, which can introduce additional interface polarization effects and enhance the scattering and attenuation of electromagnetic waves. On the basis of boron nitride coating, the surface of nanowires is further modified by silane coupling agent, which can significantly improve the interfacial compatibility between nanowires and insulating matrix. 3-Aminopropylmethyldimethoxysilane molecules contain active groups, which can react chemically with the surface of boron nitride to form stable covalent bonds. The surface of nanowires modified by silanization presents lipophilic groups, which have better affinity with organic insulating matrix, and can achieve uniform dispersion of nanowires in the matrix and effective stress transmission. Good interface bonding can inhibit the agglomeration of nanowires and give full play to the electromagnetic shielding and insulation enhancement of nanowires. Fe3O4 nanowires are prepared by hydrothermal method. By adjusting the ratio of reactants and reaction conditions, the aspect ratio, diameter and crystallinity of nanowires can be controlled. Fe3O4 nanowires with high aspect ratio can form a conductive network at a lower filling amount, and the boron nitride coating can effectively block the direct contact between nanowires and prevent the formation of a conductive network. This unique microstructure can provide a large number of interfacial polarization sites while ensuring the insulation of the material, thereby enhancing the scattering and absorption of electromagnetic waves. The soft magnetic properties of Fe3O4 nanowires and the high resistance properties of the boron nitride layer can synergistically enhance the electromagnetic shielding effect and achieve electromagnetic interference suppression in a wide frequency range. In addition, surface-modified boron nitride-coated nanowires can also improve the mechanical properties of insulating materials. The one-dimensional nanowire structure has a high aspect ratio and mechanical strength, which can play a reinforcing role in the matrix. The boron nitride coating and surface silanization can enhance the interfacial bonding between the nanowires and the matrix and achieve effective stress transfer. The orientation and interlocking effect of the nanowires can improve the strength and toughness of the material, while the boron nitride insulating layer can prevent the expansion of cracks between the nanowires and improve the fracture toughness. This reinforcement mechanism can give the cable insulation material excellent flexibility and impact resistance, meeting the requirements of the VR device use environment.In summary, the present invention uses surface-modified boron nitride to coat Fe3O4 nanowires, which can enhance the electromagnetic shielding performance, insulation performance and mechanical properties of VR equipment cable insulation materials through multiple mechanisms. Boron nitride insulation coating and surface silanization modification can synergistically improve the electromagnetic shielding effectiveness and interface compatibility of nanowires, and achieve uniform dispersion and effective stress transfer of nanowires in the insulating matrix. The core-shell structure formed by the Fe3O4 nanowire core and the boron nitride coating can introduce multiple interface polarizations and enhance the scattering and absorption of electromagnetic waves. At the same time, the one-dimensional nanowire structure and surface modification can enhance the mechanical properties of the insulating material and improve its flexibility and impact resistance. The high-performance electromagnetic shielding insulation composite material prepared by the present invention is expected to break through the bottleneck of VR equipment cable transmission and promote the further development of VR technology. This study provides new ideas and methods for the development of multifunctional electromagnetic shielding insulation materials.
[0019] In VR equipment, cable insulation materials not only need to have excellent electrical insulation, but also must have high flexibility to adapt to the frequent bending and movement of the equipment. The present invention cleverly uses di-tert-butyl peroxide to initiate a cross-linking reaction between low-density polyethylene and butadiene-styrene copolymer, thereby significantly improving the comprehensive performance of the material. Di-tert-butyl peroxide is a commonly used organic peroxide initiator, which is easy to undergo homolysis under heating conditions to generate tert-butyloxy free radicals. These highly active free radicals can attack the CH bonds on the macromolecular chains of low-density polyethylene and butadiene-styrene copolymers, and capture hydrogen atoms to generate macromolecular chain free radicals. The macromolecular chain free radicals can directly couple to form intermolecular crosslinks; at the same time, the macromolecular chain free radicals can also react with the residual double bonds in the low-density polyethylene and the carbon-carbon double bonds in the butadiene-styrene copolymer to form intramolecular crosslinks. This free radical-induced cross-linking reaction can form a stable covalent bond between the low-density polyethylene and the butadiene-styrene copolymer, tightly connecting the two polymers together, and significantly improving the flexibility and impact resistance of the material. The cross-linking reaction can not only improve the mechanical properties of the insulating material, but also improve its insulation performance. Low-density polyethylene is a non-polar material with excellent electrical insulation, but its resistance to electrical treeing is poor. Due to the presence of styrene units, butadiene-styrene copolymer contains a certain number of polar groups in the molecule, which helps to improve the material's resistance to electrical treeing. Cross-linking low-density polyethylene with butadiene-styrene copolymer can improve the material's resistance to electrical treeing while maintaining the high insulation strength of polyethylene, and reduce insulation failure caused by electrical treeing under high electric fields. The formation of a cross-linked network can also hinder the migration of charges in the insulating material, increase the volume resistivity, and reduce dielectric loss. In addition, after cross-linking low-density polyethylene and butadiene-styrene copolymer, the heat resistance of the material is also significantly improved. The presence of the cross-linked network limits the movement of the polymer chain and increases the heat deformation temperature of the material. The improvement in heat resistance allows the insulating material to maintain stable performance in more demanding environments, expanding its scope of application. In summary, the present invention utilizes di-tert-butyl peroxide to initiate a cross-linking reaction between low-density polyethylene and butadiene-styrene copolymer, which not only improves the flexibility of VR equipment cable insulation materials, but also improves their insulation performance and heat resistance. This high-performance insulation material can meet the demanding use requirements of VR equipment and is expected to promote the further development and popularization of VR technology. The material design ideas and modification methods adopted in the present invention provide new ideas for the development of new cable insulation materials.
[0020] 2,2,4-trimethyl-1,2-dihydroquinoline polymer and ethoxyquinoline are two important additives that can effectively improve the aging resistance and antioxidant properties of VR equipment cable insulation materials. Among them, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, as an excellent antioxidant, can broaden the use temperature range of insulating materials and extend their service life. The polymer molecule contains multiple quinoline ring structures, which can capture the free radicals generated during the aging process of the polymer, interrupt the aging reaction chain, and thus inhibit the aging and degradation of the material. Ethoxyquinoline, as a highly efficient antioxidant, can prevent oxygen from oxidizing and degrading insulating materials. The phenolic hydroxyl group in the ethoxyquinoline molecule can react with the free radicals generated during the oxidation process to generate stable free radical intermediates, thereby terminating the oxidation reaction chain. In addition, ethoxyquinoline can also form coordination bonds with metal ions, passivate metal catalysts, and further inhibit the oxidation reaction. The synergistic effect of the two additives can comprehensively enhance the aging resistance and oxidation resistance of VR equipment cable insulation materials, maintain their excellent insulation and mechanical properties, extend the service life of the cable, and provide reliable guarantee for the long-term stable operation of VR equipment.
[0021] The present invention also provides a method for preparing a high-flexibility insulating material for a VR device cable, comprising the following steps: S1. According to the ratio, the surface-modified banana leaf-shaped boron nitride, the surface-modified boron nitride-coated Fe3O4 nanowires, dioctyl phthalate and ethylene-vinyl acetate copolymer were fed into the reactor and stirred at a speed of 2000 to 3000 r / min for 20 to 40 min to mix evenly; S2. Low-density polyethylene, butadiene-styrene copolymer and di-tert-butyl peroxide are added to the reactor and stirred at high speed for 15 to 30 minutes to mix evenly; S3. The flexible flame-retardant block copolymer, 2,2,4-trimethyl-1,2-dihydroquinoline polymer and ethoxyquinoline were added to the reactor and stirred at a speed of 3000 to 4000 r / min for 20 to 30 min to obtain a uniformly mixed raw material; S4. The uniformly mixed raw materials are put into a screw extruder, and the extruder temperature is set to 160-180°C. After extrusion, a highly flexible insulating material for VR device cables is obtained.
[0022] (3) Beneficial technical effects 1. The ternary block copolymer contains three flame retardant groups, silicon, phosphorus and nitrogen. Through the synergistic carbonization effect between them, it not only greatly improves the flame retardant properties of the material, but also gives the material excellent mechanical properties. The synergistic carbonization effect promotes the formation of a dense carbon layer, which insulates and blocks the release of combustible gases, effectively reduces the combustion intensity, and has a higher flame retardant effect than traditional flame retardants. The amorphous molecular structure improves the interface bonding force, reduces microscopic defects, and makes the modified material have higher impact strength and flexibility.
[0023] 2. Banana leaf-shaped boron nitride is a new type of nanofiller that combines the high strength of one-dimensional nanotubes and the high toughness of two-dimensional nanosheets. The hollow tubular trunk bears the load, improving the tensile and compressive strength and fracture toughness; the edges of the graphene-like structure give excellent flexibility and impact resistance; the high insulation performance forms an "insulating island" that blocks the conductive path, improving the insulation resistance; the low dielectric constant reduces the polarization degree and signal attenuation distortion, and improves the transmission rate. Vinyltrimethoxysilane molecules are used to modify the surface of banana leaf-shaped boron nitride. Through silane chemical bonding and the introduction of vinyl groups, the dispersion of the filler and the affinity with the matrix are significantly improved. The modified filler can be evenly dispersed in the matrix, exerting the synergistic enhancement of physical entanglement and chemical bonding, effectively transferring stress, and improving the mechanical, insulation and thermal conductivity of the composite material.
[0024] 3. The present invention proposes a new composite material of surface-modified boron nitride coated Fe3O4 nanowires, which is used to enhance the comprehensive performance of VR equipment cable insulation materials. Compared with the prior art, the material shows significant advantages in electromagnetic shielding effect, dielectric properties, insulation properties and mechanical properties. High aspect ratio Fe3O4 nanowires are prepared by a hydrothermal method, and a boron nitride layer with excellent insulation properties is coated on its surface to form a core-shell structure. The boron nitride layer can effectively block the direct contact between nanowires, reduce charge transfer and energy loss, and introduce additional interface polarization effects to enhance the scattering and attenuation of electromagnetic waves. On this basis, 3-aminopropylmethyldimethoxysilane is used to silanize the surface of the nanowires, and the affinity and interface bonding force between the nanowires and the insulating matrix are significantly improved through chemical bonding. This is not only conducive to the uniform dispersion of the nanowires in the matrix, giving full play to their electromagnetic shielding and insulation enhancement effects, but also can achieve effective stress transfer, giving the material excellent flexibility and impact resistance. The present invention cleverly utilizes the soft magnetic properties of the Fe3O4 nanowire core, the high resistance properties of the boron nitride coating, and the interfacial compatibility of the surface silanization. The synergistic effect between the multiple components can achieve efficient electromagnetic interference suppression in a wide frequency range. The present invention provides a new solution for the upgrading of cable insulation materials for VR equipment, which is expected to significantly improve the signal transmission quality and reliability of VR systems, and promote the widespread application of VR technology in personal entertainment, education and training, industrial design and other fields. At the same time, the surface coating and modification strategies adopted by the present invention have certain implications for the design and preparation of other functional composite materials, and provide new ideas for the development of high-performance electromagnetic shielding materials.
[0025] 4. Aiming at the use requirements of VR equipment cable insulation materials, the present invention innovatively uses di-tert-butyl peroxide to initiate the cross-linking reaction of low-density polyethylene and butadiene-styrene copolymer, and combines the synergistic effect of 2,2,4-trimethyl-1,2-dihydroquinoline polymer and ethoxyquinoline additives to significantly improve the comprehensive performance of the insulation material. Based on the technical challenges faced by VR equipment cable insulation materials, the present invention starts from multiple aspects such as filler optimization, surface interface regulation, matrix modification, and additive selection to systematically improve material performance, providing key support for the research and development and application of a new generation of VR equipment. This composite material is expected to greatly expand the application space of VR technology and promote the leapfrog development of the virtual reality industry. At the same time, the material design ideas and modification methods adopted in the present invention provide universal guidance for the development of high-performance electromagnetic shielding insulation materials, and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the infrared Fourier transform FTIR spectrum of the flexible block flame retardant copolymer prepared in Example 1 of the present invention.
[0027] Figure 2 This is a transmission electron microscope (TEM) morphology image of the banana leaf-shaped boron nitride prepared in Example 1 of the present invention.
[0028] Figure 3 This is the XRD phase analysis diagram of the banana leaf-shaped boron nitride prepared in Example 1 of the present invention.
[0029] Figure 4 This is the TEM morphology of the Fe3O4 nanowires prepared in Example 1 of the present invention.
[0030] Figure 5 This is the TEM morphology of the boron nitride-coated Fe3O4 nanowires prepared in Example 1 of the present invention.
[0031] Figure 6 This is the XRD phase analysis diagram of the boron nitride-coated Fe3O4 nanowires prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0033] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0034] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0035] Example 1 A highly flexible insulating material for VR equipment cables, comprising the following components by weight: 5 parts of a flexible block flame-retardant copolymer, 3 parts of surface-modified banana leaf-shaped boron nitride, 4 parts of surface-modified boron nitride-coated Fe3O4 nanowires, 30 parts of low-density polyethylene, 45 parts of butadiene-styrene copolymer, 0.2 parts of di-tert-butyl peroxide, 2 parts of ethylene-vinyl acetate copolymer, 1.0 parts of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 0.5 parts of ethoxyquinoline, and 1.5 parts of dioctyl phthalate; The flexible block flame-retardant copolymer is obtained by copolymerization of piperazine phosphate, melamine phosphate and diphenyl (siloxane and polysiloxane); the surface-modified banana leaf-shaped boron nitride is obtained by surface-modifying banana leaf-shaped boron nitride with vinyltrimethoxysilane; the surface-modified boron nitride-coated Fe3O4 nanowires are obtained by surface-modifying boron nitride with 3-aminopropylmethyldimethoxysilane to coat Fe3O4 nanowires.
[0036] The preparation method of the flexible block flame-retardant copolymer is as follows: after mixing 48 parts of piperazine phosphate and 16 parts of melamine phosphate by weight, the binary block copolymer is obtained after dehydration reaction for 2 hours. 30 parts of diphenylsilanediol are placed in a vacuum oven, dehydrated at 160°C for 1 hour, taken out of the vacuum oven and crushed in a grinder to obtain diphenyl (siloxane and polysiloxane). At room temperature, 50 parts of the binary block copolymer and 2 parts of diphenyl (siloxane and polysiloxane) are mixed evenly and placed in a vacuum oven, dehydrated at 250°C for 60 minutes, and then the temperature is reduced to 50°C, and the product is crushed in a crusher to obtain a flexible block copolymer.
[0037] The preparation method of surface modified banana leaf-shaped boron nitride is as follows: in parts by weight, at room temperature, 6 parts of sodium nitrate and 50 parts of concentrated sulfuric acid with a mass fraction of 80% are mixed uniformly, then 10 parts of multi-walled boron nitride nanotubes and 3 parts of potassium permanganate are added, and then stirred for 90 minutes, and then the mixed solution is heated to 40°C and stirred for 25 minutes, and then 90 parts of deionized water are added, and the mixed solution is heated to 80°C, and continued to be stirred for 30 minutes, and then 3% hydrogen peroxide is added drop by drop, and the addition is stopped when the mixed solution does not generate gas, and then the filter residue is collected by vacuum filtration, and then the filter residue is washed with deionized water for 4 times, and finally the washed filter residue is vacuum dried at room temperature to obtain banana leaf-shaped boron nitride. The preparation method of hydroxy-grafted banana leaf-shaped boron nitride is as follows: by weight, 2 parts of banana leaf-shaped boron nitride are dispersed in 30 parts of 5 mol / L sodium hydroxide aqueous solution, and then stirred at 150°C for 4 hours. After the reaction is completed, the solution is filtered to obtain a filter residue, and then the filter residue is rinsed with deionized water to a pH of 7, and finally dried completely in a vacuum drying oven at room temperature to obtain hydroxy-grafted banana leaf-shaped boron nitride. Prepare 40 parts of 90% ethanol aqueous solution by volume, and then adjust the solution pH to 4 with acetic acid, then add 2 parts of vinyl trimethoxysilane, stir at room temperature for 30 minutes, then add 3 parts of hydroxy-grafted banana leaf-shaped boron nitride, stir at 50°C for 60 minutes, then filter to obtain a filter residue, and then wash the filter residue with deionized water three times, and finally vacuum dry at 110°C for 4 hours to obtain surface-modified banana leaf-shaped boron nitride.
[0038] The preparation method of surface modified boron nitride coated nanowires is as follows: by weight, 3 parts of ferrous sulfate and 2 parts of sodium thiosulfate are added to a Teflon-lined autoclave, and then 10 parts of polyethylene glycol, 20 parts of deionized water and 10 parts of sodium hydroxide are added, followed by heat preservation at 140°C for 20 hours, and then the solid product is separated by centrifugation, and then the solid product is washed three times with ethanol, and finally dried completely at room temperature under vacuum to obtain Fe3O4 nanowires. After 10 parts of sodium borohydride and 13 parts of ammonium chloride are dissolved in 100 parts of deionized water and mixed evenly, 20 parts of Fe3O4 nanowires are added thereto, stirred at room temperature for 60 minutes, and then the solution is filtered to separate the solid powder and dried completely in a vacuum drying oven at room temperature, and then the completely dried solid powder is placed in a tubular furnace, and heat-treated at 500°C for 60 minutes in an ammonia atmosphere to obtain boron nitride coated Fe3O4 nanowires. 3 parts of Fe3O4 nanowires coated with boron nitride were added to 100 parts of a mixed solution of ethanol and water in a mass ratio of 1:1, and then 1.0 parts of 3-aminopropylmethyldimethoxysilane was added, followed by magnetic stirring for 5 hours. Finally, the solid powder was filtered and dried completely in a vacuum drying oven at room temperature.
[0039] The present invention also provides a method for preparing a high-flexibility insulating material for a VR device cable, comprising the following steps: S1. According to the ratio, the surface-modified banana leaf-shaped boron nitride, the surface-modified boron nitride-coated Fe3O4 nanowires, dioctyl phthalate and ethylene-vinyl acetate copolymer were fed into the reactor and stirred at a speed of 2000r / min for 20min to mix evenly; S2. Low-density polyethylene, butadiene-styrene copolymer and di-tert-butyl peroxide were added to the reactor and stirred at high speed for 15 min to mix evenly; S3. The flexible flame-retardant block copolymer, 2,2,4-trimethyl-1,2-dihydroquinoline polymer and ethoxyquinoline were added to the reactor and stirred at a speed of 3000 r / min for 20 min to obtain a uniformly mixed raw material; S4. The uniformly mixed raw materials are put into a screw extruder, and the extruder temperature is set to 160° C. After extrusion, a highly flexible insulating material for VR device cables is obtained.
[0040] In Example 1 of the present invention, a boron nitride coated Fe3O4 nanowire reinforced flexible block flame retardant copolymer composite material was successfully prepared. Infrared Fourier transform FTIR spectrum ( Figure 1 ) at 1128cm -1 and 719cm -1 The new weak peaks appearing at the positions correspond to the stretching vibration peak of Si-Ph and the characteristic peak of -Ph2SiO-, which confirms that the silicon-containing component has been successfully introduced into the flexible block flame-retardant copolymer molecules. Transmission electron microscopy TEM morphology ( Figure 2 ) clearly shows that the prepared boron nitride has a banana leaf-like structure, and its XRD phase analysis diagram ( Figure 3 ) further proves that boron nitride is a hexagonal crystal. The TEM morphology of Fe3O4 nanowires is as follows Figure 4 As shown in Figure 2, the morphology after boron nitride coating is as follows: Figure 5 shown. Figure 6 The XRD phase analysis diagram of Fe3O4 nanowires coated with boron nitride is given, which confirms that the prepared nanowire composite is composed of hexagonal boron nitride and Fe3O4. In summary, the embodiment of the present invention uses characterization methods such as infrared spectroscopy, transmission electron microscopy and X-ray diffraction to fully prove the successful preparation of Fe3O4 nanowires coated with boron nitride reinforced flexible block flame retardant copolymer composites, which provides a new idea for the design and synthesis of high-performance polymer-based composites.
[0041] Example 2 A highly flexible insulating material for VR equipment cables, comprising the following components by weight: 6 parts of flexible block flame-retardant copolymer, 5 parts of surface-modified banana leaf-shaped boron nitride, 6 parts of surface-modified boron nitride-coated Fe3O4 nanowires, 38 parts of low-density polyethylene, 50 parts of butadiene-styrene copolymer, 0.4 parts of di-tert-butyl peroxide, 3 parts of ethylene-vinyl acetate copolymer, 1.8 parts of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 0.9 parts of ethoxyquinoline, and 2.1 parts of dioctyl phthalate; The flexible block flame-retardant copolymer is obtained by copolymerization of piperazine phosphate, melamine phosphate and diphenyl (siloxane and polysiloxane); the surface-modified banana leaf-shaped boron nitride is obtained by surface-modifying banana leaf-shaped boron nitride with vinyltrimethoxysilane; the surface-modified boron nitride-coated Fe3O4 nanowires are obtained by surface-modifying boron nitride with 3-aminopropylmethyldimethoxysilane to coat Fe3O4 nanowires.
[0042] The preparation method of the flexible block flame-retardant copolymer is as follows: after 55 parts of piperazine phosphate and 20 parts of melamine phosphate are mixed uniformly by weight, a binary block copolymer is obtained after a dehydration reaction for 2.6 hours. 35 parts of diphenylsilanediol are placed in a vacuum oven, dehydrated at 172°C for 1.6 hours, taken out of the vacuum oven and crushed in a grinder to obtain diphenyl (siloxane and polysiloxane). At room temperature, 56 parts of the binary block copolymer and 3 parts of diphenyl (siloxane and polysiloxane) are mixed uniformly and placed in a vacuum oven, dehydrated at 265°C for 78 minutes, and then the temperature is reduced to 65°C, and the product is crushed in a grinder to obtain a flexible block copolymer.
[0043] The preparation method of surface modified banana leaf-shaped boron nitride is as follows: in parts by weight, at room temperature, 8 parts of sodium nitrate and 59 parts of concentrated sulfuric acid with a mass fraction of 80% are mixed uniformly, then 15 parts of multi-walled boron nitride nanotubes and 5 parts of potassium permanganate are added, and then stirred for 99 minutes, and then the mixed solution is heated to 43°C and stirred for 30 minutes, and then 90 parts of deionized water are added, and the mixed solution is heated to 83°C, and continued to be stirred for 36 minutes, and then 3% hydrogen peroxide is added drop by drop, and the addition is stopped when the mixed solution does not generate gas, and then the filter residue is collected by vacuum filtration, and then the filter residue is washed with deionized water for 4 times, and finally the washed filter residue is vacuum dried at room temperature to obtain banana leaf-shaped boron nitride. The preparation method of hydroxy-grafted banana leaf-shaped boron nitride is as follows: by weight, 3 parts of banana leaf-shaped boron nitride are dispersed in 36 parts of 5 mol / L sodium hydroxide aqueous solution, and then stirred at 159°C for 5.2 hours. After the reaction is completed, the solution is filtered to obtain a filter residue, and then the filter residue is rinsed with deionized water to a pH of 7, and finally dried completely in a vacuum drying oven at room temperature to obtain hydroxy-grafted banana leaf-shaped boron nitride. 46 parts of 90% ethanol aqueous solution are prepared, and then the pH of the solution is adjusted to 4 with acetic acid, followed by adding 2.6 parts of vinyl trimethoxysilane, stirring at room temperature for 39 minutes, and then adding 4 parts of hydroxy-grafted banana leaf-shaped boron nitride, stirring at 56°C for 69 minutes, and then filtering to obtain a filter residue, and then washing the filter residue with deionized water three times, and finally vacuum drying at 116°C for 4.6 hours to obtain surface-modified banana leaf-shaped boron nitride.
[0044] The preparation method of surface modified boron nitride coated nanowires is as follows: by weight, 4.5 parts of ferrous sulfate and 3.2 parts of sodium thiosulfate are added to a Teflon-lined autoclave, and then 10 parts of polyethylene glycol, 20 parts of deionized water and 13 parts of sodium hydroxide are added, followed by heat preservation at 146°C for 25 hours, and then the solid product is separated by centrifugation, and then the solid product is washed three times with ethanol, and finally dried completely at room temperature under vacuum to obtain Fe3O4 nanowires. After 12 parts of sodium borohydride and 15 parts of ammonium chloride are dissolved in 100 parts of deionized water and mixed evenly, 28 parts of Fe3O4 nanowires are added thereto, stirred at room temperature for 78 minutes, and then the solution is filtered to separate the solid powder and dried completely in a vacuum drying oven at room temperature, and then the completely dried solid powder is placed in a tubular furnace, and heat-treated at 530°C for 78 minutes in an ammonia atmosphere to obtain boron nitride coated Fe3O4 nanowires. 4.5 parts of Fe3O4 nanowires coated with boron nitride were added to 100 parts of a mixed solution of ethanol and water in a mass ratio of 1:1, and then 1.8 parts of 3-aminopropylmethyldimethoxysilane were added, followed by magnetic stirring for 6.5 hours. Finally, the solid powder was filtered and dried completely in a vacuum drying oven at room temperature.
[0045] The present invention also provides a method for preparing a high-flexibility insulating material for a VR device cable, comprising the following steps: S1. According to the ratio, the surface-modified banana leaf-shaped boron nitride, the surface-modified boron nitride-coated Fe3O4 nanowires, dioctyl phthalate and ethylene-vinyl acetate copolymer were fed into the reactor and mixed at a speed of 2300r / min for 26min; S2. Low-density polyethylene, butadiene-styrene copolymer and di-tert-butyl peroxide were added to the reactor and stirred at high speed for 20 min to mix evenly; S3. The flexible flame-retardant block copolymer, 2,2,4-trimethyl-1,2-dihydroquinoline polymer and ethoxyquinoline were added to the reactor and stirred at a speed of 3300 r / min for 23 min to obtain a uniformly mixed raw material; S4. The uniformly mixed raw materials are put into a screw extruder, and the extruder temperature is set to 166° C. After extrusion, a highly flexible insulating material for VR device cables is obtained.
[0046] Example 3 A highly flexible insulating material for VR equipment cables, comprising the following components by weight: 8 parts of a flexible block flame-retardant copolymer, 6 parts of surface-modified banana leaf-shaped boron nitride, 8 parts of surface-modified boron nitride-coated Fe3O4 nanowires, 45 parts of low-density polyethylene, 54 parts of butadiene-styrene copolymer, 0.6 parts of di-tert-butyl peroxide, 4 parts of ethylene-vinyl acetate copolymer, 2.5 parts of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 1.3 parts of ethoxyquinoline, and 2.7 parts of dioctyl phthalate; The flexible block flame-retardant copolymer is obtained by copolymerization of piperazine phosphate, melamine phosphate and diphenyl (siloxane and polysiloxane); the surface-modified banana leaf-shaped boron nitride is obtained by surface-modifying banana leaf-shaped boron nitride with vinyltrimethoxysilane; the surface-modified boron nitride-coated Fe3O4 nanowires are obtained by surface-modifying boron nitride with 3-aminopropylmethyldimethoxysilane to coat Fe3O4 nanowires.
[0047] The preparation method of the flexible block flame-retardant copolymer is as follows: after 61 parts of piperazine phosphate and 24 parts of melamine phosphate are mixed uniformly by weight, a binary block copolymer is obtained after a dehydration reaction for 3 hours. 39 parts of diphenylsilanediol are placed in a vacuum oven, dehydrated at 184°C for 2 hours, taken out of the vacuum oven and crushed in a grinder to obtain diphenyl (siloxane and polysiloxane). At room temperature, 62 parts of the binary block copolymer and 4 parts of diphenyl (siloxane and polysiloxane) are mixed uniformly and placed in a vacuum oven, dehydrated at 280°C for 96 minutes, and then the temperature is reduced to 80°C, and the product is crushed in a crusher to obtain a flexible block copolymer.
[0048] The preparation method of surface modified banana leaf-shaped boron nitride is as follows: in parts by weight, at room temperature, 10 parts of sodium nitrate and 68 parts of concentrated sulfuric acid with a mass fraction of 80% are mixed uniformly, then 19 parts of multi-walled boron nitride nanotubes and 7 parts of potassium permanganate are added, and then stirred for 108 minutes, and then the mixed solution is heated to 46°C and stirred for 34 minutes, and then 90 parts of deionized water are added, and the mixed solution is heated to 86°C, and continued to be stirred for 42 minutes, and then 3% hydrogen peroxide is added drop by drop, and the addition is stopped when the mixed solution does not generate gas, and then the filter residue is collected by vacuum filtration, and then the filter residue is washed with deionized water for 4 times, and finally the washed filter residue is vacuum dried at room temperature to obtain banana leaf-shaped boron nitride. The preparation method of hydroxy-grafted banana leaf-shaped boron nitride is as follows: by weight, 4 parts of banana leaf-shaped boron nitride are dispersed in 42 parts of 5 mol / L sodium hydroxide aqueous solution, and then stirred at 168°C for 6 hours. After the reaction is completed, the solution is filtered to obtain a filter residue, and then the filter residue is rinsed with deionized water to a pH of 7, and finally dried completely in a vacuum drying oven at room temperature to obtain hydroxy-grafted banana leaf-shaped boron nitride. Prepare 52 parts of 90% ethanol aqueous solution by volume, and then adjust the solution pH to 4 with acetic acid, then add 3 parts of vinyl trimethoxysilane, stir at room temperature for 48 minutes, then add 5 parts of hydroxy-grafted banana leaf-shaped boron nitride, stir at 62°C for 78 minutes, then filter to obtain a filter residue, and then wash the filter residue with deionized water three times, and finally vacuum dry at 122°C for 5 hours to obtain surface-modified banana leaf-shaped boron nitride.
[0049] The preparation method of surface modified boron nitride coated Fe3O4 nanowires is as follows: by weight, 6 parts of ferrous sulfate and 5 parts of sodium thiosulfate are added to a Teflon-lined autoclave, and then 10 parts of polyethylene glycol, 20 parts of deionized water and 16 parts of sodium hydroxide are added, followed by heat preservation at 152°C for 29 hours, and then the solid product is separated by centrifugation, and then the solid product is washed three times with ethanol, and finally dried completely at room temperature under vacuum to obtain Fe3O4 nanowires. After 14 parts of sodium borohydride and 17 parts of ammonium chloride are dissolved in 100 parts of deionized water and mixed evenly, 35 parts of Fe3O4 nanowires are added thereto, stirred at room temperature for 96 minutes, and then the solution is filtered to separate the solid powder and dried completely in a vacuum drying oven at room temperature, and then the completely dried solid powder is placed in a tubular furnace, and heat-treated at 560°C for 96 minutes in an ammonia atmosphere to obtain boron nitride coated Fe3O4 nanowires. 6 parts of Fe3O4 nanowires coated with boron nitride were added to 100 parts of a mixed solution of ethanol and water in a mass ratio of 1:1, and then 2.5 parts of 3-aminopropylmethyldimethoxysilane were added, followed by magnetic stirring for 8 hours. Finally, the solid powder was filtered and dried completely in a vacuum drying oven at room temperature.
[0050] The present invention also provides a method for preparing a high-flexibility insulating material for a VR device cable, comprising the following steps: S1. According to the ratio, the surface-modified banana leaf-shaped boron nitride, the surface-modified boron nitride-coated Fe3O4 nanowires, dioctyl phthalate and ethylene-vinyl acetate copolymer were fed into the reactor and mixed at a speed of 2600r / min for 32min; S2. Low-density polyethylene, butadiene-styrene copolymer and di-tert-butyl peroxide were added to the reactor and stirred at high speed for 24 min to mix evenly; S3. The flexible flame-retardant block copolymer, 2,2,4-trimethyl-1,2-dihydroquinoline polymer and ethoxyquinoline were added to the reactor and stirred at a speed of 3600 r / min for 26 min to obtain a uniformly mixed raw material; S4. The uniformly mixed raw materials are put into a screw extruder, and the extruder temperature is set to 172°C. After extrusion, a highly flexible insulating material for VR device cables is obtained.
[0051] Example 4 A highly flexible insulating material for VR equipment cables, comprising the following components by weight: 10 parts of a flexible block flame-retardant copolymer, 8 parts of surface-modified banana leaf-shaped boron nitride, 10 parts of surface-modified boron nitride-coated Fe3O4 nanowires, 55 parts of low-density polyethylene, 60 parts of butadiene-styrene copolymer, 0.9 parts of di-tert-butyl peroxide, 5 parts of ethylene-vinyl acetate copolymer, 3.5 parts of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 1.8 parts of ethoxyquinoline, and 3.5 parts of dioctyl phthalate; The flexible block flame-retardant copolymer is obtained by copolymerization of piperazine phosphate, melamine phosphate and diphenyl (siloxane and polysiloxane); the surface-modified banana leaf-shaped boron nitride is obtained by surface-modifying banana leaf-shaped boron nitride with vinyltrimethoxysilane; the surface-modified boron nitride-coated Fe3O4 nanowires are obtained by surface-modifying boron nitride with 3-aminopropylmethyldimethoxysilane to coat Fe3O4 nanowires.
[0052] The preparation method of the flexible block flame-retardant copolymer is as follows: after 70 parts of piperazine phosphate and 30 parts of melamine phosphate are mixed uniformly by weight, a binary block copolymer is obtained after a dehydration reaction for 4 hours. After 45 parts of diphenylsilanediol are placed in a vacuum oven, dehydrated at 200°C for 3 hours, the mixture is taken out of the vacuum oven and crushed in a grinder to obtain diphenyl (siloxane and polysiloxane). At room temperature, 70 parts of the binary block copolymer and 6 parts of diphenyl (siloxane and polysiloxane) are mixed uniformly and placed in a vacuum oven, dehydrated at 300°C for 120 minutes, and then the temperature is reduced to 100°C, and the product is crushed in a crusher to obtain a flexible block copolymer.
[0053] The preparation method of surface modified banana leaf-shaped boron nitride is as follows: by weight, at room temperature, 12 parts of sodium nitrate and 80 parts of concentrated sulfuric acid with a mass fraction of 80% are mixed evenly, then 25 parts of multi-walled boron nitride nanotubes and 9 parts of potassium permanganate are added, and then stirred for 120 minutes, and then the mixed solution is heated to 50°C and stirred for 40 minutes, and then 90 parts of deionized water are added, and the mixed solution is heated to 90°C, and continued to be stirred for 50 minutes, and then 3% hydrogen peroxide is added drop by drop, and the addition is stopped when the mixed solution does not generate gas, and then the filter residue is collected by vacuum filtration, and then the filter residue is washed with deionized water for 4 times, and finally the washed filter residue is vacuum dried at room temperature to obtain banana leaf-shaped boron nitride. The preparation method of hydroxy-grafted banana leaf-shaped boron nitride is as follows: by weight, 5 parts of banana leaf-shaped boron nitride are dispersed in 50 parts of 5 mol / L sodium hydroxide aqueous solution, and then stirred at 180°C for 8 hours. After the reaction is completed, the solution is filtered to obtain a filter residue, and then the filter residue is rinsed with deionized water to a pH of 7, and finally dried completely in a vacuum drying oven at room temperature to obtain hydroxy-grafted banana leaf-shaped boron nitride. 60 parts of 90% ethanol aqueous solution are prepared, and then the pH of the solution is adjusted to 4 with acetic acid, followed by adding 4 parts of vinyl trimethoxysilane, stirring at room temperature for 60 minutes, and then adding 7 parts of hydroxy-grafted banana leaf-shaped boron nitride, stirring at 70°C for 90 minutes, and then filtering to obtain a filter residue, and then washing the filter residue with deionized water three times, and finally vacuum drying at 130°C for 6 hours to obtain surface-modified banana leaf-shaped boron nitride.
[0054] The preparation method of surface-modified boron nitride coated Fe3O4 nanowires is as follows: by weight, 8 parts of ferrous sulfate and 6 parts of sodium thiosulfate are added to a Teflon-lined autoclave, and then 10 parts of polyethylene glycol, 20 parts of deionized water and 20 parts of sodium hydroxide are added, followed by heat preservation at 160°C for 35 hours, and then the solid product is separated by centrifugation, and then the solid product is washed three times with ethanol, and finally dried completely at room temperature under vacuum to obtain Fe3O4 nanowires. After 16 parts of sodium borohydride and 20 parts of ammonium chloride are dissolved in 100 parts of deionized water and mixed evenly, 45 parts of Fe3O4 nanowires are added thereto, stirred at room temperature for 120 minutes, and then the solution is filtered to separate the solid powder and dried completely in a vacuum drying oven at room temperature, and then the completely dried solid powder is placed in a tubular furnace, and heat-treated at 600°C for 120 minutes in an ammonia atmosphere to obtain boron nitride coated Fe3O4 nanowires. 8 parts of Fe3O4 nanowires coated with boron nitride were added to 100 parts of a mixed solution of ethanol and water in a mass ratio of 1:1, and then 3.5 parts of 3-aminopropylmethyldimethoxysilane were added, followed by magnetic stirring for 10 hours. Finally, the solid powder was filtered and dried completely in a vacuum drying oven at room temperature.
[0055] This embodiment also provides a method for preparing a high-flexibility insulating material for a VR device cable, comprising the following steps: S1. According to the ratio, the surface-modified banana leaf-shaped boron nitride, the surface-modified boron nitride-coated Fe3O4 nanowires, dioctyl phthalate and ethylene-vinyl acetate copolymer were fed into the reactor and stirred at a speed of 3000r / min for 40min to mix evenly; S2. Low-density polyethylene, butadiene-styrene copolymer and di-tert-butyl peroxide were added to the reactor and stirred at high speed for 30 min to mix evenly; S3. The flexible flame-retardant block copolymer, 2,2,4-trimethyl-1,2-dihydroquinoline polymer and ethoxyquinoline were added to the reactor and stirred at a speed of 4000 r / min for 30 min to obtain a uniformly mixed raw material; S4. The uniformly mixed raw materials are put into a screw extruder, and the extruder temperature is set to 180°C. After extrusion, a highly flexible insulating material for VR device cables is obtained.
[0056] Example 5 It is basically the same as Example 1, except that the amount of surface-modified banana leaf-shaped boron nitride added to the high-flexibility insulating material of the VR device cable is 10 parts.
[0057] Comparative Example 1 It is basically the same as Example 1, except that the flexible block flame retardant copolymer is not added to the high-flexibility insulating material for preparing the VR device cable.
[0058] Comparative Example 2 It is basically the same as Example 1, except that an equal amount of surface-modified boron nitride nanotubes is added to the high-flexibility insulating material for preparing the VR device cable, so the surface-modified boron nitride nanotubes are surface-modified original boron nitride nanotubes, and the nanotubes are not coated with Fe3O4 nanowires.
[0059] The preparation method of surface modified boron nitride is as follows: 2 parts of boron nitride nanotubes are dispersed in 30 parts of 5 mol / L sodium hydroxide aqueous solution by weight, and then stirred at 150°C for 4 hours. After the reaction is completed, the solution is filtered to obtain a filter residue, and then the filter residue is rinsed with deionized water to a pH of 7, and finally dried completely in a vacuum drying oven at room temperature to obtain hydroxy-grafted boron nitride. 40 parts of 90% ethanol aqueous solution are prepared, and then the pH of the solution is adjusted to 4 with acetic acid, followed by adding 2 parts of vinyltrimethoxysilane, stirring at room temperature for 30 minutes, and then adding 3 parts of hydroxy-grafted boron nitride, stirring at 50°C for 60 minutes, followed by filtering to obtain a filter residue, and then washing the filter residue with deionized water three times, and finally vacuum drying at 110°C for 4 hours to obtain surface modified boron nitride.
[0060] Comparative Example 3 It is basically the same as Example 1, except that an equal amount of banana leaf-shaped boron nitride is added to the high-flexibility insulating material for preparing the VR device cable, so the banana leaf-shaped boron nitride is not surface-modified.
[0061] Comparative Example 4 It is basically the same as Example 1, except that an equal amount of boron nitride coated Fe3O4 nanowires is added to the high-flexibility insulating material for preparing the VR device cable, so the boron nitride coated Fe3O4 nanowires are not surface modified.
[0062] Comparative Example 5 It is basically the same as Example 1, except that an equal amount of Fe3O4 nanowires is added to the high-flexibility insulating material for preparing the VR device cable, so the surface of the Fe3O4 nanowires is not coated with surface-modified boron nitride.
[0063] Characterization Tests: Tensile performance evaluation: In accordance with the requirements of the national standard GB / T 2951.12, the mechanical properties of the samples are tested using an advanced tensile testing system. Under standardized specimen size, a uniform tensile force is applied to the sample until it breaks. This process can accurately record and calculate the tensile strength of the sample and the elongation at break. This test program is designed to comprehensively evaluate the mechanical bearing capacity of the material and its ductility during stress.
[0064] Flame retardant property verification: Based on the internationally recognized UL94 fire test standard, a specific experiment was designed to evaluate the flame retardant effect of the sample. During the experiment, the sample was directly exposed to the flame, and its combustion behavior and self-extinguishing ability were carefully observed to quantitatively evaluate the safety performance and fireproof performance of the material in a fire environment.
[0065] Volume resistivity measurement: The volume resistivity characteristics of the material at 20°C are tested in strict accordance with the guidelines of GB / T 1410-2006 standard. This test ensures the accuracy and reliability of the resistivity data obtained, providing an important basis for the evaluation of the electrical insulation performance of the material.
[0066] Electromagnetic shielding effectiveness analysis: In order to evaluate the electromagnetic shielding performance of highly flexible insulating materials, a high-performance vector network analyzer E5071C was used, and the experiment was carried out according to the test method in the GB / T 32596-2016 standard. In the experiment, the composite material was first finely ground into powder, then mixed with paraffin in a ratio (1:3) and ground again until uniform. Then, the mixed powder was pressed into a 2 mm thick ring specimen using a mold and fixed on a copper probe for testing. The test covered a wide frequency range of 2 to 18 GHz to comprehensively examine the electromagnetic shielding effectiveness of the material in different frequency bands.
[0067] The properties of the high-flexibility insulating materials of Examples 1 to 5 and Comparative Examples 1 to 5 are summarized in Table 2.
[0068] Table 2 Performance parameters of high-flexibility insulating materials
[0069] The main difference between Comparative Example 1 and Example 1 is that no flexible block flame-retardant copolymer is added. As can be seen from Table 2, the tensile strength and elongation at break of Example 1 are significantly higher than those of Comparative Example 1, and the flame retardant property is improved from V-1 level to V-0 level, because the addition of the flexible block flame-retardant copolymer improves the flexibility of the matrix through block copolymerization on the one hand, and the phosphorus and silicon flame-retardant groups introduced into its molecular structure give the material excellent flame retardant properties on the other hand.
[0070] The main difference between Comparative Example 2 and Example 1 is that surface-modified boron nitride nanotubes are added. As can be seen from Table 2, the tensile strength, elongation at break, dielectric strength and electromagnetic shielding effectiveness of Example 1 are significantly better than those of Comparative Example 2. This is because after surface modification, the flexible chain segments grafted on the surface of banana leaf-shaped boron nitride can form a stronger interface interaction with the matrix, significantly improving the mechanical properties of the composite material. At the same time, the modified banana leaf-shaped boron nitride has better dispersibility in the matrix, and the formed heat-insulating flame-retardant layer and insulating layer are more uniform and dense, thereby showing better flame retardancy, insulation and electromagnetic shielding properties.
[0071] The main difference between Comparative Example 3 and Example 1 is that the added material is banana leaf-shaped boron nitride without surface modification. As can be seen from Table 2, the comprehensive performance of Example 1 is superior to that of Comparative Example 3. This is because after the flexible chain segments are grafted onto the surface, the banana leaf-shaped boron nitride can form a strong interface bond with the substrate, thereby significantly enhancing the mechanical properties of the material. In addition, the modified banana leaf-shaped boron nitride can migrate to the surface of the substrate to form a dense heat-insulating flame-retardant layer when heated, while inducing directional charge migration, greatly improving the flame retardancy, insulation and electromagnetic shielding properties of the material.
[0072] The main difference between Comparative Example 4 and Example 1 is that the boron nitride coated Fe3O4 nanowires without surface modification are added. As can be seen from Table 2, the mechanical properties, insulation properties and electromagnetic shielding properties of Example 1 are better than those of Comparative Example 4. This is because the surface-grafted flexible segments can improve the compatibility of the boron nitride coated Fe3O4 nanowires with the matrix, promote the uniform dispersion of the nanowires in the matrix, and form an interpenetrating network structure, thereby effectively transmitting stress, blocking crack propagation, and improving the strength and toughness of the material. At the same time, the modification significantly enhances the insulation shielding effect of the boron nitride layer.
[0073] The main difference between Comparative Example 5 and Example 1 is that Fe3O4 nanowires without boron nitride coating are added. After coating with boron nitride, the mechanical properties of the insulating material are improved. At the same time, after coating with boron nitride, the conductivity of the Fe3O4 nanowires is reduced, and the electromagnetic loss mechanism is changed from conductive loss to dielectric loss and multiple scattering, thereby significantly improving the shielding effectiveness.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A highly flexible insulating material for VR device cables, characterized in that: The composition comprises the following components in parts by weight: 5-10 parts of flexible block flame-retardant copolymer, 3-8 parts of surface-modified banana leaf-shaped boron nitride, 4-10 parts of surface-modified boron nitride-coated Fe3O4 nanowires, 30-55 parts of low-density polyethylene, 45-60 parts of butadiene-styrene copolymer, 0.2-0.9 parts of di-tert-butyl peroxide, 2-5 parts of ethylene-vinyl acetate copolymer, 1.0-3.5 parts of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 0.5-1.8 parts of ethoxyquinoline, and 1.5-3.5 parts of dioctyl phthalate; The flexible flame-retardant block copolymer is obtained by copolymerization of piperazine phosphate, melamine phosphate and diphenyl (siloxane and polysiloxane); The surface-modified banana leaf-shaped boron nitride is obtained by surface-modifying banana leaf-shaped boron nitride with vinyltrimethoxysilane; The surface-modified boron nitride coated Fe3O4 nanowires are obtained by surface-modifying the boron nitride coated Fe3O4 nanowires with 3-aminopropylmethyldimethoxysilane.
2. The highly flexible insulating material for VR device cables according to claim 1, characterized in that: The preparation method of the flexible block flame-retardant copolymer is as follows: by weight, at room temperature, 50-70 parts of a binary block copolymer and 2-6 parts of diphenyl (siloxane and polysiloxane) are uniformly mixed and placed in a vacuum oven, dehydrated at 250-300° C. for 60-120 minutes, and then the temperature is reduced to 50-100° C., and the product is crushed in a crusher to obtain a flexible block copolymer; The preparation method of the binary block copolymer is as follows: by weight, 48 to 70 parts of piperazine phosphate and 16 to 30 parts of melamine phosphate are uniformly mixed, and then dehydrated for 2 to 4 hours to obtain the binary block copolymer.
3. The highly flexible insulating material for VR device cables according to claim 2, characterized in that: The preparation method of the diphenyl (siloxane and polysiloxane) is as follows: 30 to 45 parts by weight of diphenylsilanediol are placed in a vacuum oven, dehydrated at 160 to 200° C. for 1 to 3 hours, then taken out of the vacuum oven and crushed in a grinder to obtain diphenyl (siloxane and polysiloxane).
4. The highly flexible insulating material for VR device cables according to claim 1, characterized in that: The preparation method of the surface modified banana leaf-shaped boron nitride is as follows: by weight, 40 to 60 parts of an ethanol aqueous solution with a volume fraction of 90% are prepared, and then the pH value of the solution is adjusted to 4 with acetic acid, followed by adding 2 to 4 parts of vinyltrimethoxysilane, stirring at room temperature for 30 to 60 minutes, and then adding 3 to 7 parts of hydroxyl-grafted banana leaf-shaped boron nitride, stirring at 50 to 70° C. for 60 to 90 minutes, and then filtering to obtain a filter residue, and then washing the filter residue with deionized water for three times, and finally vacuum drying at 110 to 130° C. for 4 to 6 hours to obtain the surface modified banana leaf-shaped boron nitride.
5. The highly flexible insulating material for VR device cables according to claim 4, characterized in that: The preparation method of the hydroxy-grafted banana leaf-shaped boron nitride is as follows: by weight, 2 to 5 parts of banana leaf-shaped boron nitride are dispersed in 30 to 50 parts of a 5 mol / L sodium hydroxide aqueous solution, and then stirred at 150 to 180° C. for 4 to 8 hours. After the reaction is completed, the solution is filtered to obtain a filter residue, and then the filter residue is rinsed with deionized water to a pH of 7, and finally dried completely in a vacuum drying oven at room temperature to obtain the hydroxy-grafted banana leaf-shaped boron nitride.
6. The highly flexible insulating material for VR device cables according to claim 5, characterized in that: The preparation method of the banana leaf-shaped boron nitride is as follows: by weight, at room temperature, 6-12 parts of sodium nitrate and 50-80 parts of concentrated sulfuric acid with a mass fraction of 80% are evenly mixed, then 10-25 parts of multi-walled boron nitride nanotubes and 3-9 parts of potassium permanganate are added, and then stirred for 90-120 minutes, and then the mixed solution is heated to 40-50°C and stirred for 25-40 minutes, and then 90 parts of deionized water are added, and the mixed solution is heated to 80-90°C, and the stirring is continued for 30-50 minutes, and then 3% hydrogen peroxide is added drop by drop, and the addition is stopped after the mixed solution does not generate gas, and then the filter residue is collected by vacuum filtration, and then the filter residue is washed with deionized water for 4 times, and finally the washed filter residue is vacuum dried at room temperature.
7. The highly flexible insulating material for VR device cables according to claim 1, characterized in that: The preparation method of the surface modified boron nitride coated Fe3O4 nanowires is as follows: 3 to 8 parts of boron nitride coated Fe3O4 nanowires are added to 100 parts of a mixed solution of ethanol and water in a mass ratio of 1:1, and then 1.0 to 3.5 parts of 3-aminopropylmethyldimethoxysilane are added, followed by magnetic stirring for 5 to 10 hours, and finally the solid powder is filtered and dried completely in a vacuum drying oven at room temperature.
8. The highly flexible insulating material for VR device cables according to claim 7, characterized in that: The preparation method of the boron nitride coated Fe3O4 nanowires is as follows: by weight, 10 to 16 parts of sodium borohydride and 13 to 20 parts of ammonium chloride are dissolved in 100 parts of deionized water and mixed evenly, 20 to 45 parts of Fe3O4 nanowires are added thereto, stirred at room temperature for 60 to 120 minutes, and then the solution is filtered to separate the solid powder and dried completely in a vacuum drying oven at room temperature, and then the completely dried solid powder is placed in a tubular furnace, and heat treated at 500 to 600° C. for 60 to 120 minutes in an ammonia atmosphere to obtain the boron nitride coated Fe3O4 nanowires.
9. The highly flexible insulating material for VR device cables according to claim 8, characterized in that: The preparation method of the Fe3O4 nanowires is as follows: 3 to 8 parts of ferrous sulfate and 2 to 6 parts of sodium thiosulfate are added to a Teflon-lined autoclave by weight, and then 10 parts of polyethylene glycol, 20 parts of deionized water and 10 to 20 parts of sodium hydroxide are added, followed by keeping warm at 140 to 160°C for 20 to 35 hours, and then centrifuging the solid product, washing the solid product three times with ethanol, and finally drying it completely under vacuum at room temperature to obtain Fe3O4 nanowires.
10. A method for preparing a highly flexible insulating material for VR device cables according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. According to the ratio, the surface-modified banana leaf-shaped boron nitride, the surface-modified boron nitride-coated Fe3O4 nanowires, dioctyl phthalate and ethylene-vinyl acetate copolymer were fed into the reactor and stirred at a speed of 2000 to 3000 r / min for 20 to 40 min to mix evenly; S2. Low-density polyethylene, butadiene-styrene copolymer and di-tert-butyl peroxide are added to the reaction vessel and stirred for 15 to 30 minutes to mix evenly; S3. The flexible flame-retardant block copolymer, 2,2,4-trimethyl-1,2-dihydroquinoline polymer and ethoxyquinoline were added to the reactor and stirred at a speed of 3000 to 4000 r / min for 20 to 30 min to obtain a uniformly mixed raw material; S4. The uniformly mixed raw materials are put into a screw extruder, and the extruder temperature is set to 160-180°C. After extrusion, a highly flexible insulating material for VR device cables is obtained.
Citation Information
Patent Citations
Preparation method for cross-linked polyethylene water resistant tree insulation material
CN101367972A
Preparation method of boron nitride-coated carbon nanotubes
CN103172050A
Photovoltaic cable and preparation method thereof
CN111171465A
In-situ synthesized boron nitride nanosheet-nanotube composite material and preparation method thereof
CN111747385A
Multi-block or random copolymerized halogen-free flame-retardant macromolecule and flame-retardant polyolefin material thereof
CN114181397A
Cited By
Thermoplastic elastomer with high dielectric constant and preparation method thereof
CN119859297A
